Systemic delivery of calcium channel blockers for hypertension through transdermal delivery - a review - AL-japairai, Khater Ahmed Saeed; Mahmood, Syed (Trans Tech Publications Ltd, Switzerland, 2021)
Hypertension is a significant public health challenge, responsible for a substantial proportion of deaths and disability globally. Calcium Channel Blockers (CCBs) are an essential class for the treatment of hypertension. However, most of CCBs must be taken more than once daily due to their low oral bioavailability and limited half-life leading to non-compliance in patients. The development of delivery methods for CCBs is an ongoing effort to overcome the issues related to their delivery via their traditional forms. The administration of the drug through the skin for systemic delivery has been recognised as one of the potential routes in hypertension treatment, especially when drugs suffer from low bioavailability, undesirable side effects and short biological half-life following oral administration. The main limitation of transdermal drug delivery is the resistance barrier of skin layers to penetrant molecules. Remarkable research efforts have been made worldwide to minimise the skin barrier and to create transdermal systems of several CCBs via employing skin-enhancing potential. The persistent progress in this field is promising for development the transdermal dosage forms advance technology in the long term and being commercialised sooner rather than later. This review explores the investigations on the viability and applicability of systemic delivery of numerous CCBs through the skin.